2009
DOI: 10.1074/jbc.m109.017376
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Potential Greatly Enhances Superoxide Generation by the Cytochrome bc1 Complex Reconstituted into Phospholipid Vesicles

Abstract: The mitochondrial cytochrome bc 1 complex (ubiquinol/cytochrome c oxidoreductase) is generally thought to generate superoxide anion that participates in cell signaling and contributes to cellular damage in aging and degenerative disease. However, the isolated, detergent-solubilized bc 1 complex does not generate measurable amounts of superoxide except when inhibited by antimycin. In addition, indirect measurements of superoxide production by cells and isolated mitochondria have not clearly resolved the contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
70
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 41 publications
10
70
0
Order By: Relevance
“…Both reaction schemes require as an initiation a reduced state of heme b L , which is consistent with the observation that ROS are observed when the electron transfer between heme b L and heme b H is impeded by blocking the Q i site with antimycin or by increase in membrane potential (144,218). In the semiforward scheme, reduced heme b L is unable to take electron from USQ o and thus cannot convert it to UQ (103,145,189,209).…”
Section: Generation Of Reactive Oxygen Speciessupporting
confidence: 80%
“…Both reaction schemes require as an initiation a reduced state of heme b L , which is consistent with the observation that ROS are observed when the electron transfer between heme b L and heme b H is impeded by blocking the Q i site with antimycin or by increase in membrane potential (144,218). In the semiforward scheme, reduced heme b L is unable to take electron from USQ o and thus cannot convert it to UQ (103,145,189,209).…”
Section: Generation Of Reactive Oxygen Speciessupporting
confidence: 80%
“…On the basis of these and other data, it was proposed that under hypoxic conditions the interaction of UQCRB with cytochrome b could prolong QH · lifetime at the Qo site of complex III, thereby enhancing generation and release of ROS into the intermembrane space and cytosol (FIGURE 5B). Since terpestacin also caused mitochondrial depolarization (916) and ROS production by complex III was increased by hyperpolarization (1665), it was further speculated that hypoxic prolongation of QH · lifetime at Qo was due to decreased electron transfer from cytochrome b L to b H , perhaps as a result of mitochondrial hyperpolarization (916) (FIGURE 5B). Consistent with this possibility, two laboratories have reported that hypoxia caused mitochondrial hyperpolarization in PASMC (1278,1814); however, another found that hypoxia had no effect on ⌬⌿ M (2032).…”
Section: Mitochondriamentioning
confidence: 99%
“…Therefore, we propose that during hypoxia, terpestacin bound to UQCRB of Complex III may mimic a condition where partially oxidized ubiquinone pool slows down the forward electron transfer to induce a reverse electron transfer onto O 2 by reduced heme b L , resulting in the prolonged lifetime of SQ at the Q o pocket, thereby enhancing the probability of superoxide production as was the case with antimycin-induced ROS production (23,30). In addition, recent evidence has revealed that the membrane potential enhances the formation of superoxide from Complex III by opposing electron transfer from heme b L to b H (33). Indeed, the binding of terpestacin to UQCRB decreases the mitochondrial membrane potential as shown in Fig.…”
Section: Terpestacin Modulates the O 2 -Sensing Function Of Complex Imentioning
confidence: 99%